Hubungan Literasi Fisik dengan Motivasi Mengikuti Aktivitas Olahraga Pada Mahasiswa Jurusan Pendidikan Jasmani - I WAYAN PERDI IRAWAN (Jurnal Riset Multidisiplin Edukasi, 2025)
The decline in student participation in physical activities at the university level has become a growing concern, particularly among students in Physical Education programs who are expected to model an active lifestyle. This study aims to analyze the relationship between physical literacy and student motivation in engaging in sports activities, both within and outside the academic setting. A quantitative correlational approach was employed, involving 120 students selected through purposive sampling. The research instruments included two validated and reliable scales: one measuring physical literacy and the other measuring motivation for sports participation. The findings revealed that most students demonstrated moderate to high levels of physical literacy. However, only a small portion reported high motivation to participate in independent physical activities. The Pearson correlation test showed a positive and significant relationship between physical literacy and motivation to engage in sports activities (r = 0.611, p < 0.05). These results indicate that a higher level of physical literacy contributes to increased student motivation to engage in physical activities. This study highlights the importance of integrating conceptual understanding of physical literacy with practical learning strategies so that students not only understand the importance of physical activity but also adopt it as part of their lifestyle. The findings can serve as a foundation for developing physical education policies in higher education that are based on physical literacy.